Lingual nerve neuropathy: more than just third molar surgery and inferior alveolar nerve blocks - Ngeow, Wei Cheong; Chai, Wen Lin (George Warman Publications, 2019)
Neuropathy of the lingual nerve, when it occurs, often results from third molar surgery, or the provision of inferior alveolar nerve blocks. Investigators have reported that the anatomical location and the unpredictable course of the lingual nerve play important roles in it being affected by these procedures. However, there are many other causes of neuropathy with which most medical and dental practitioners are unfamiliar. This article briefly reviews the course of the lingual nerve, and summarizes the causes and reports of all uncommon aetiologies of neuropathy that can occur along the path of a lingual nerve. The clinical implication and management of lingual nerve neuropathy is discussed. © 2019 George Warman Publications. All rights reserved.